Quantitative Analysis of Qualitative Information From Interviews: A Systematic Literature Review. (April 2014) - Fakis, Apostolos; Hilliam, Rachel; Stoneley, Helen; Townend, Michael
Background: A systematic literature review was conducted on mixed methods area.Objectives: The overall aim was to explore how qualitative information from interviews has been analyzed using quantitative methods.Methods: A contemporary review was undertaken and based on a predefined protocol. The references were identified using inclusion and exclusion criteria and specific key terms in 11 search databases.Results: Evidence was synthesized from 14 references that included the methods used for quantifying qualitative information, analyzing it statistically and the rationale behind this. Gaps in the existing literature and recommendations for future research were identified.Conclusions: This review highlights the need for a new mixed method based on advanced statistical modeling method that will explore complex relationships arising from qualitative information.